The Effectiveness of Intermittent Pneumatic Compression for Delayed Onset Muscle Soreness in Active People: A Literature Review - Vida Nanda Chattalia; Ni Nyoman Mekar Sari (Universitas Udayana dan Diaspora Taipei Medical University, 2022)
Introduction: When the exercises we perform exceed the muscle endurance threshold, Delayed Onset Muscle Soreness (DOMS) often occurs. DOMS is pain that a person feels 24 to 48 hours after strenuous physical activity or heavy and intense physical activity that can lead to damage to muscles and other connective tissues in the form of small tears in the muscles, muscle spasms, overstretching, and can cause tendon and connective tissue tears. Symptoms produced by DOMS conditions are certainly alarming for daily activities. This literature review will discuss ways to reduce DOMS conditions by using Intermittent Pneumatic Compression to overcome these conditions. Methods: The method in this study used a literature review based on the study results of data sources (including PubMed, ScienceDirect, NCBI, and Google Scholar) database with a publication period from 2017 to 2022. Keywords used in the search: [“Delayed Onset Muscle Soreness,” “DOMS” or “Muscle Soreness”] and [“Intermittent Pneumatic Compression” or “Recovery Pump”]. Results: We found three related articles: two randomized controlled trials and one cross-over design based on the search result. The studies examined the effectiveness of Intermittent Pneumatic Compression on Delayed Onset Muscle Soreness. In the results of the three studies, Intermittent Pneumatic Compression offered little to no benefit in the recovery of DOMS inactive people. Conclusion: All studies concluded Intermittent Pneumatic Compression was not effective in reducing Delayed Onset Muscle Soreness.